STRUCTURAL ANALYSIS OF BODY COMPOSITION STATUS IN ABU DHABI POLICE PERSONNEL - Kukic, Filip; Dopsaj, Milivoj (NBP. Nauka, bezbednosti, policija, 2017)
Monitoring of morphological status is necessary because human body structure is very important and at the same time biologically very changeable category that can be influenced by many external and internal factors. The purpose of this study is a structural analysis of current state of body composition for purposes of establishing initial body composition model of Abu Dhabi police. Measurement procedures have been conducted under the monitoring of Strategic Management & Performance Improvement Department, Sports Activity Section, Abu Dhabi police, in the gym for police officers with help of the machine In Body 720. The sample size was 59 police officers of different age and rank. Main characteristics of the sample were: age 31.53±9.42 years, height (H) 173.08±6.13cm and body weight (BW) 80.10±11.50kg. Investigated variables were: height (H), body weight (BW), body mass index (BMI), body fat mass (BFM), percent body fat (PBF), skeletal muscle mass (SMM) and percent of skeletal muscle mass (%SMM). Results statistically were calculated by descriptive statistics and cluster analysis. Results have shown that prevalence of overweighed according to WHO was 59.06%, prevalence of obesity according to ACE was 49.15% and 66.10% of the sample had under average %SMM.